gH625 is a viral derived peptide for effective delivery of intrinsically disordered proteins - Smaldone G (Dove Medical Press, 2013)
Giovanni Smaldone,1,2 Annarita Falanga,3 Domenica Capasso,4 Daniela Guarnieri,5,6 Stefania Correale,1,7 Massimiliano Galdiero,8 Paolo A Netti,4 Massimo Zollo,9 Stefania Galdiero,1,2 Sonia Di Gaetano,1 Emilia Pedone1 1Institute of Biostructures and Bioimaging, National Research Council, Naples, Italy; 2Department of Pharmacy and Interuniversity Research Center on Bioactive Peptides, Federico II University of Naples, Naples, Italy; 3Molecular Diagnostics and Pharmaceuticals Scarl, Naples, Italy; 4Special Center for Biotechnology, Federico II University of Naples, Naples, Italy; 5Center for Advanced Biomaterials for Health Care, Interdisciplinary Research Centre on Biomaterials, Italian Institute of Technology, Naples, Italy; 6Interdisciplinary Research Centre on Biomaterials, Federico II University of Naples, Naples, Italy; 7Kedrion S.p.A, Sant'antimo, Naples, Italy; 8Department of Experimental Medicine, Federico II University of Naples, Naples, Italy; 9CEINGE – Advanced Biotechnology Scarl, Naples, Italy Abstract: A genetically modified recombinant gH625-c-prune was prepared through conjugation of c-prune with gH625, a peptide encompassing 625–644 residues of the glycoprotein H of herpes simplex virus 1, which has been proved to possess the ability to carry cargo molecules across cell membranes. C-prune is the C-terminal domain of h-prune, overexpressed in breast, colorectal, and gastric cancers, interacting with multiple partners, and representing an ideal target for inhibition of cancer development. Its C-terminal domain results in an intrinsically disordered domain (IDD), and the peculiar properties of gH625 render it an optimal candidate to act as a carrier for this net negatively charged molecule by comparison with the positively charged TAT. A characterization of the recombinant gH625-c-prune fusion protein was conducted by biochemical, cellular biology and confocal microscopy means in comparison with TAT-c-prune. The results showed that the gH625-c-prune exhibited the ability to cross biomembranes, opening a new scenario on the use of gH625 as a novel multifunctional carrier. Keywords: delivery, IDP